Reinforcement theory analysis on training and development / Dr. Baderisang Mohamed, Mohd. Sukor Md. Yusoff and Nur Azmina Salimi Uzair - Mohamed, Baderisang; Md. Yusoff, Mohd. Sukor; Salimi Uzair, Nur Azmina (Universiti Teknologi MARA, Kedah, 2022)
According to the reinforcement theory, an organisation's success is determined by its people's knowledge, skills, training, and development. The effectiveness of employees in learning new skills and information is influenced by their learning practices. Thus, the focus of this paper is on individual’s learning theories and implications. A literature review was carried out, as well as logical justifications and explanations. This paper found that cognitive-based techniques, non-cognitive approaches, and needs-based approaches can help reduce and modify undesired behaviours. By promoting behaviour through positive training and growth, the reinforcement theory can improve an individual’s performance.